The 7E Learning Cycle Approach to Understand Thermal Phenomena (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
Conceptual understanding is often a problem in science learning, and this issue has become the point of science education experts, including in Indonesia. Lately, ten articles in Indonesia and six articles in other countries have discussed the model of the 7E Learning Cycle. It was mentioned that this model is able to increase learners’ conceptual understanding. This research intended to reveal the effectivity of physics learning using the 7E Learning Cycle in improving students’ understanding of temperature and heat concepts. The research design is quasi-experimental with a non-equivalent control group design. The sample was senior high school students. Objective test in the form of multiple choices equipped with reason was employed as the data collection instrument. Based on the data analysis, the value of Effect Size was 0.5 and belonged to the medium category. In other words, the use of the 7E Learning Cycle model is sufficient to improve the learners’ understanding of temperature and heat concepts. This could be seen from the success of the learning process that integrates the whole seven stages with the seven indicators of conceptual understanding in detail. Thus, the 7E Learning Cycle could be effectively applied and can increase the students’ conceptual understanding.